2016
DOI: 10.1016/j.ces.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

The shape and behaviour of a granular bed in a rotating drum using Eulerian flow fields obtained from PEPT

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…It can take on one of a number of regimes such as slumping, rolling, cascading, cataracting and centrifuging. By measuring the flowing angle or speed, all of these regimes can be characterised (MiDi, 2004;Fischer et al, 2008;Morrison et al, 2016). For cohesive powders, determining these parameters is difficult due to the irregular surface of the flow and the lack of a continuous regime.…”
Section: Rotating Drummentioning
confidence: 99%
“…It can take on one of a number of regimes such as slumping, rolling, cascading, cataracting and centrifuging. By measuring the flowing angle or speed, all of these regimes can be characterised (MiDi, 2004;Fischer et al, 2008;Morrison et al, 2016). For cohesive powders, determining these parameters is difficult due to the irregular surface of the flow and the lack of a continuous regime.…”
Section: Rotating Drummentioning
confidence: 99%
“…[ 2 ] introduced PEPT for engineering flow assessment. Since that time PEPT has been used to evaluate flow in milling equipment [ 3 ], hydrocyclones [ 4 ], and dishwashers [ 5 ], among other engineering apparatuses but has not been extensively used for biomedical purposes. The majority of PEPT evaluations have used the Birmingham method [ 2 ] and tracked a single particle.…”
Section: Introductionmentioning
confidence: 99%
“…Research outcomes of the transverse solids motion in rotating cylinders can be used as references. Various types of behavior that a bed of solids can exhibit, as described by Mellmann, 28 Ding et al 38 and Morrison et al, 39 may similarly appear in a domestic tumble dryer. Textile motion in rotating drums will experience sliding, rolling, cascading, cataracting (falling) and centrifuging (rotating) under various drying conditions.…”
mentioning
confidence: 97%
“…A large number of researches have found that these modes are mostly determined by the Froude number (Fr, ! 2 R=g), the load fraction (f load , V m =V d ) and the critical wall friction coefficient ( w,c , 2 sin 3 25,26,29,39 The textile macroscale, at the level of a single textile piece, is concerned with the mixing textile interactions and the forces acting on textiles due to their dynamics in the rotating drum. Much of the work on the mixing behavior of particles is applicable at this scale, among which the most relevant chemical engineering processes are granular flow [40][41][42] and tumbling ball mills.…”
mentioning
confidence: 99%